Optimal Stocking Density Cultivating Catfish (Clarias gariepinus) in Round Pond Media on a Household Scale - Khumaidi, Achmad; Muqsith, Abdul; Wafi, Abdul; Nur Aisyah Jamil, Siti (Department of Aquaculture, 2025)
Increasing stocking density in catfish cultivation is part of efforts to increase production to meet catfish needs nationally and internationally. The obstacles faced by household scale cultivators when applying high stocking densities are poor water quality, high feed conversion, slow growth and high mortality. Many novice cultivators on a household scale are tempted by high production results by implementing very high stocking densities, but do not yet understand the cultivation techniques well. This research aims to determine the optimal stocking density for cultivating catfish on a household scale using round tarpaulin ponds. The study used a completely randomized design of four treatments with three replications (250 fish/m3, 500 fish/m3, 750 fish/m3 and 1000 fish/m3). The cultivation container used is a tarpaulin pool with a diameter of 3 meters, and the fish are given commercial feed with 28-33% protein. Production results are also analyzed using the business income analyst model. A stocking density of 500 fish/m3 produces the most optimal production values, namely absolute growth of 4.28 ± 0.02%/day, absolute length growth of 12.4 ± 0.9 cm, survival of 85.97 ± 0.56%, feed conversion of 0.95 ± 0.00, and production of 30.4 ± 0.57 kg/m3 with operating income of Rp. 1,258,967,-. The results of the analysis of production and income values show that treatment with a density of 500 fish/m3 is the best stocking density for cultivating catfish on a household scale using tarpaulin ponds.